2020
DOI: 10.1029/2020wr027951
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Transformation of Mercury Across a Dammed Boreal River Are Linked to Carbon Processing and Hydrology

Abstract: Reservoirs are known to accelerate the mobilization and cycling of mercury and carbon as a result of flooding of terrestrial organic matter, which can lead to environmental concerns at local and broader spatial scales. We explored the covariation of mercury (Hg) and carbon (C) functional pools in natural and recently dammed portions of the aquatic network of the Romaine River watershed in Northern Quebec, Canada, to understand how the fate of these elements varies across systems with contrasting hydrology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Relationships between [MeHg] and δ 13 C have been observed for lake organisms, , with pelagic organisms having higher [MeHg] and lower δ 13 C compared to littoral organisms. , Few studies have related organism [MeHg] to δ 13 C in streams or rivers. One reason is that the δ 13 C range is generally larger in lakes than in rivers because of the higher methanogenesis and CO 2 recycling in lakes and related methylation. ,, We found only one study in lotic environments that observed δ 13 C to be a better predictor than δ 15 N for determining Hg accumulation in stream macroinvertebrates . The authors linked this observation to, at least in part, scrapers and filterers foraging in sun-exposed sites characterized by a higher production of periphytic biofilm (low δ 13 C and high Hg) as compared with invertebrates in shaded sites that forage on land detritus (high δ 13 C and low Hg).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Relationships between [MeHg] and δ 13 C have been observed for lake organisms, , with pelagic organisms having higher [MeHg] and lower δ 13 C compared to littoral organisms. , Few studies have related organism [MeHg] to δ 13 C in streams or rivers. One reason is that the δ 13 C range is generally larger in lakes than in rivers because of the higher methanogenesis and CO 2 recycling in lakes and related methylation. ,, We found only one study in lotic environments that observed δ 13 C to be a better predictor than δ 15 N for determining Hg accumulation in stream macroinvertebrates . The authors linked this observation to, at least in part, scrapers and filterers foraging in sun-exposed sites characterized by a higher production of periphytic biofilm (low δ 13 C and high Hg) as compared with invertebrates in shaded sites that forage on land detritus (high δ 13 C and low Hg).…”
Section: Resultsmentioning
confidence: 91%
“… , At DOC concentrations higher than 10 mg/L, a negative relationship with MeHg concentrations in water and organisms has sometimes been observed, in part related to the lower Hg bioavailability if bound to DOC. The bacterial respiration has also been shown to respectively plateau or decline at the highest DOC and TP ranges from several lakes (>10 mg/L and >11 μg/L, respectively) . We suggest to more often include the measurement of CO 2 concentrations in future Hg studies to better explain the DOC vs MeHg relationships …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The model was based on 1078 samples originating from various Québec aquatic ecosystems from temperate and boreal climates. The model validated 5 distinct components (De Bonville et al, 2020; Supplementary Fig. 1), described in Table 1 as the excitation and emission fluorescence peaks.…”
Section: Dom Optical Propertiesmentioning
confidence: 89%
“…Overall, in freshwater systems, the concentration of mercury compounds increases concomitantly with the increasing concentration of OM (Wetzel, 2001). Specifically, MeHg and/or total mercury (T-Hg) concentrations have been shown to be positively related to DOC (dissolved organic carbon), and more precisely to the concentration of aromatic molecules in the OM pool (Watras et al, 1998;Braaten et al, 2014;Lavoie et al, 2019;De Bonville et al, 2020), with the latter often considered to be of allochthonous origin (Lapierre and Del Giorgio, 2014). In fact, Hg has a high affinity for molecules containing reduced sulfur such as thiols, and the availability of these molecules in the system may control Hg-DOC associations and co-transport (Skyllberg et al, 2003;Ravichandran, 2004;French et al, 2014).…”
Section: Mehg and Organic Matter A Parallel Fate In Lakes And Reservoirsmentioning
confidence: 99%